2020
DOI: 10.1364/boe.383721
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast differentiation of bone marrow stromal cells by femtosecond laser bone ablation

Abstract: This study examines the osteogenic effect of femtosecond laser bone ablation on bone mesenchymal stromal cells (BMSCs). Three-week old Sprague-Dawley (SD) rats were selected for experiments. Right tibias were ablated by a 10-W femtosecond laser (treated group), whereas left tibias were not subjected to laser ablation (control group). After ablation, BMSCs of both tibias were cultured and purified separately. Cell proliferation was then analyzed, as well as the expressions of RNA and several proteins (alkaline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…28-30 OCN represents an osteogenic marker protein 31 with its expression, when upregulated, shown to be a useful aid in relation to the promotion of osteoblast differentiation. 32 As a proliferation marker, PCNA and its elevated expression has been highlighted as a hallmark of accelerated proliferation of osteoblasts in osteoporosis rats. 33 The aforementioned evidence highlights the capability of miR-136-5p to promote osteogenic proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…28-30 OCN represents an osteogenic marker protein 31 with its expression, when upregulated, shown to be a useful aid in relation to the promotion of osteoblast differentiation. 32 As a proliferation marker, PCNA and its elevated expression has been highlighted as a hallmark of accelerated proliferation of osteoblasts in osteoporosis rats. 33 The aforementioned evidence highlights the capability of miR-136-5p to promote osteogenic proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, studies have revealed that excess ROS could inhibit the osteoinductive effects by interfering with several signaling pathways such as the Wnt signaling and Hedgehog signaling systems [27]. In this study, we further probed the hMSCs with DCFDA to evaluate cellular ROS responses before and after photo‐stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, we proposed a differentiation strategy through the pure use of fsL stimulation. Several studies have found that the fsL ablation can promote mouse tibia and craniofacial skeleton regeneration [27, 28]. However, the effects of the direct interaction between fsL and stem cells have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The process of fracture healing requires the production of a large number of new osteoblasts, which accelerates bone synthesis and calcification, and increases bone volume and density [ 27 ]. As the body ages, the number of ABMSCs functional cells decreases, and their potential to differentiate into osteoblasts in the bone marrow is down-regulated [ 28 , 29 ]. Meanwhile, senescence-related secretory phenotypic molecules act in the bone microenvironment and inhibit the osteogenic differentiation of ABMSCs.…”
Section: Discussionmentioning
confidence: 99%